Facilitating the Dissemination of iCBT for the Treatment of Anxiety and Depression: A Feasibility Study. Issue 3 (18th June 2018) - DaPonte, Daniella; Talbot, France; Titov, Nickolai; Dear, Blake F.; Hadjistavropoulos, Heather D.; Hadjistavropoulos, Thomas; Jbilou, Jalila
Abstract: Translating existing internet-based cognitive-behavioural therapy (iCBT), along with the use of transdiagnostic and self-guided formats, may prove to be a cost-effective option of disseminating iCBT. Only recently have encouraging findings been reported for a self-guided delivery. This study assessed the feasibility of a French and self-guided version of an existing English iCBT course, called the Wellbeing Course, for the treatment of anxiety and depression. Existing ICBT programs have not yet been delivered in French, although this language is spoken worldwide. Thirty-one participants were included in a single group pre-post open trial with a 3-month follow-up. Feasibility outcomes were attrition, treatment adherence, acceptability, and preliminary efficacy. Primary outcome measures were the Patient Health Questionnaire 9-item (PHQ-9) and the Generalised Anxiety Disorder 7-item (GAD-7). Nearly 75% of the participants completed the program. Over 80% of the participants provided posttreatment and follow-up data. All study completers reported that they would recommend the Wellbeing Course to a friend having similar problems. Significant reductions in symptoms of anxiety and depression were found following treatment, consistent with earlier studies. These preliminary findings support the use of the assessed strategies to facilitate the cross-cultural dissemination of iCBT for a more universal access to quality psychological care.